Efeitos de um programa educacional para atendentes visando a independência de jovens com deficiência intelectual institucionalizados - Boueri, Iasmin Zanchi (2010)
The general aim of the present research was to evaluate the efficacy of an Educational Program with institutional caregivers trained in the work environment with the objective to teach youngsters with intellectual disabilities to be independent in daily living activities. For better design, the research was divided in two studies I and II). The objective of Study 1 was to elaborate a contingency adapted Educational Program for the institutional caregivers in their own work environment. The participants were six institutional caregivers who were working with youngsters diagnosed with intellectual disabilities. Interviews and observations were made in order to identify the daily living activities that were applied with those youngster and also the difficulties of the work done with the residents. An Educational Program proposal was elaborated from the obtained data whose objective was to soften the mentioned difficulties, as well as to promote the behavior changes in the participants, making the caregivers more capable to teach behaviors that could make the residents more independent. The objective of Study 2 was to evaluate the effects of the implementation of the Educational Program for the institutional caregivers developed during Study 1. Ten participants took part in the second study being: five intellectually disabled youngsters that inhabited in a residential institution and five direct support professionals (caregivers) that were in everyday contact with the residents. A multiple-probe design was used to verify the effects of the intervention, as it allows the demonstration of the experimental control validity, since the independent variable is introduced sequentially in different moments among the participants, and the dependent variable is measured before, during and after the implementation of the Educational Program. The frequency data recording of events served to evaluate the initial repertory and the behavior changes of the participants during and after the implementation of the caregivers in service training, and also allowed to follow up caregivers and residents performance when the intervention was no longer applied. The participants were grouped in pairs and went through all the experimental phases (baseline, probes, intervention and maintenance). The baseline and probes were developed at the same time with all pairs and the experimental phases occurred in different moments for each pair. The obtained results show that it is possible, after the implementation of an Educational Program, to modify the contingencies found in the residential institutions, making them favorable to the learning of behavior related to the development of daily living activities. When one make the contingencies favorable, it is possible to verify the development of the resident s potential, as they acquire more independence in the activities realization. The study brings out the discussion about the implementation of Educational Programs in institutions for people with intellectual disabilities.